2020
DOI: 10.18632/aging.103658
|View full text |Cite
|
Sign up to set email alerts
|

LNK deficiency decreases obesity-induced insulin resistance by regulating GLUT4 through the PI3K-Akt-AS160 pathway in adipose tissue

Abstract: In recent years, LNK, an adapter protein, has been found to be associated with metabolic diseases, including hypertension and diabetes. We found that the expression of LNK in human adipose tissue was positively correlated with serum glucose and insulin in obese people. We examined the role of LNK in insulin resistance and systemic energy metabolism using LNK-deficient mice ( LNK -/- ). With consumption of a high-fat diet, wild type (WT) mice accumulated more intrahepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In the current study, we found that GLUT4 mRNA level was elevated in LNK knockout PCOS mice. The mechanism of LNK-altered GLUT4 expression was further explored in our other work, in which similar results were found in HFD-induced insulin resistant mice [ 30 ].…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…In the current study, we found that GLUT4 mRNA level was elevated in LNK knockout PCOS mice. The mechanism of LNK-altered GLUT4 expression was further explored in our other work, in which similar results were found in HFD-induced insulin resistant mice [ 30 ].…”
Section: Discussionmentioning
confidence: 66%
“…The ethics committee for animal research in Sun Yat-sen University approved the experiments and we followed the NIH Guide for the Care and Use of Laboratory Animals [ 30 ]. Mice were kept under standard conditions (12 hours light/dark, with free access to feed and water).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations